A case of brachygnathis inferior and palatoschisis in a reindeer calf - K. Elvested; M. Nordkvist (Rangifer, 1985)
The mandibles were abnormally short and there was an opening in the hard palate, extending from the mandibular junction (corpus mandibulae) to the anterior rim of the palate bone. No other pathological findings were observed.